PENYULUHAN BAHAYA NARKOBA DAN JUDI ONLINE DI DESA KARYA UTAMA KECAMATAN CIKEDAL KABUPATEN PANDEGLANG - Jamaludin, Jamaludin; Sulaeman, Yeni; Nugraha, Rifki Arif; Mustakim, Usep Saepul (Jurnal Ilmiah Pengabdian Kepada Masyarakat, 2024)
The rise of drug abuse in people's lives today is very concerning because the impact of drug abuse not only damages the organs of the body but also damages the soul of the user. As technology evolves, so does gambling. Online gambling or gambling using technology in the form of certain applications or websites has become a widespread phenomenon in society, both in the upper economic group and in the middle and poor economic communities. The purpose of this service is to prevent the occurrence of drugs and online gambling, and to provide students and the public with an understanding of the dangers of drugs and online gambling that can harm themselves. The impact of drug abuse and online gambling can damage health, social, legal, economic, and even the future. The activity methods are the lecture and question and answer method. The result of this activity is that counseling is very effective for adolescents and the community in preventing The occurrence of drugs and online gambling, educating the public about the impact and dangers of drugs and online gambling that can be introduced to children and others